Natural products in green-detection of cancer cells, cancer therapy, and monitoring of therapeutic and cancer progression: A perspective - Islam, Muhammad (International Journal of Medicine, 2017)
The natural products embedded with the molecular framework by combining with themselves or other molecules and biological micro/macro molecules. By the help of some special techniques, that can be incorporated to identify and detect different body markers as well as pathophysiological conditions. To date, a number of cancer detection methods are available. However, an early cancer detection is still remained the key problems, which causes delay, reduction of success rate in the cancer therapy, and increased the lethality, as cancer is a complicated and a large group of related diseases. To date, due to the promising biological compatibility and safety profile, many natural products have been used as anticancer drugs. Additionally, many of them are also included in the green syntheses, especially the plant-derived products. It is due their less or even non-toxic and economic character. This text offers a perspective on the detection of cancer by using natural products, along with a therapeutic and monitoring of treatment and cancer progression, suggests that, the natural products can be considered as leading tools in overall cancer management.